Scandium(iii) complexes of monophosphorus acid DOTA analogues: a thermodynamic and radiolabelling study with 44Sc from cyclotron and from a 44Ti/44Sc generator. Issue 4 (17th December 2015) - Kerdjoudj, R.; Pniok, M.; Alliot, C.; Kubíček, V.; Havlíčková, J.; Rösch, F.; Hermann, P.; Huclier-Markai, S.
Abstract : The influence of the phosphonic/phosphinic acid pendant arm in DOTA derivatives on properties of their Sc 3+ complexes and efficiency of their 44 Sc labelling were investigated. Abstract : The complexation ability of DOTA analogs bearing one methylenephosphonic (DO3AP) or methylenephosphinic (DO3AP PrA and DO3AP ABn ) acid pendant arm toward scandium was evaluated. Stability constants of their scandium(iii ) complexes were determined by potentiometry combined with 45 Sc NMR spectroscopy. The stability constants of the monophosphinate analogues are somewhat lower than that of the Sc–DOTA complex. The phosphorus acid moiety interacts with trivalent scandium even in very acidic solutions forming out-of-cage complexes; the strong affinity of the phosphonate group to Sc(iii ) precludes stability constant determination of the Sc–DO3AP complex. These results were compared with those obtained by the free-ion selective radiotracer extraction (FISRE) method which is suitable for trace concentrations. FISRE underestimated the stability constants but their relative order was preserved. Nonetheless, as this method is experimentally simple, it is suitable for a quick relative comparison of stability constant values under trace concentrations. Radiolabelling of the ligands with 44 Sc was performed using the radioisotope from two sources, a 44 Ti/ 44 Sc generator and 44m Sc/ 44 Sc from a cyclotron. The best radiolabelling conditions for the ligands were pH = 4, 70 °C and 20 min which were, however, not superior to those of the parent DOTA. Nonetheless, in vitro behaviour of the Sc(iii ) complexes in the presence of hydroxyapatite and rat serum showed sufficient stability of 44 Sc complexes of these ligands for in vivo applications. PET images and ex vivo biodistribution of the 44 Sc–DO3AP complex performed on healthy Wistar male rats showed no specific bone uptake and rapid clearance through urine.